If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -26 = 10(18 + -6) Reorder the terms: -26 + p = 10(18 + -6) Combine like terms: 18 + -6 = 12 -26 + p = 10(12) Multiply 10 * 12 -26 + p = 120 Solving -26 + p = 120 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + p = 120 + 26 Combine like terms: -26 + 26 = 0 0 + p = 120 + 26 p = 120 + 26 Combine like terms: 120 + 26 = 146 p = 146 Simplifying p = 146
| -38-4(12)= | | -38-4(6)= | | -a+4a= | | 18+9(x)=288 | | 18+9(24)= | | x^4-9*x^3+27*x^2-91*x=0 | | 45+18= | | -3x-5=-35 | | 4a-a=23 | | x-3y+2z=-28 | | 2(x+3)=14-x | | 5(x-3)=2(4x+1) | | 3(12-x)-6=2 | | -v+3=4 | | 3x+3y+z=-11 | | 32+4(x)=180 | | 224=-8m | | 39+3(x)=174 | | 5m-2(m+2)=-(2m+14) | | 88-18=9(h-5) | | 4a+2ac+6ab=0 | | p-18=9(20-5) | | 0.25(16x-8)+6=12-5x | | 13x+9+5x+9=180 | | p+0.15p=29.5 | | p-18=9(18-5) | | Log[5]72-Log[5]x=3Log[5]2 | | 4xy-x^2+5x=0 | | p-18=9(h-5) | | 5m+4m=-9 | | 567=-21a | | -48-12(24)= |